Characterizing the marine iodine cycle and its relationship to ocean deoxygenation in an Earth system model - K. Cheng; A. Ridgwell; D. S. Hardisty (Biogeosciences)
Iodine (I) abundance in marine carbonates (measured as an elemental ratio with calcium, I /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1b4178c77ca0d4bfee6c9ddd864f3a43"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-4927-2024-ie00001.svg" width="8pt" height="14pt" src="bg-21-4927-2024-ie00001.png"/></svg:svg> Ca) is of broad interest as a proxy for local/regional ocean redox. This connection arises because the speciation of iodine in seawater, the balance between iodate (IO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="53e1f98be2cdf70dbe180d95894fc6b5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-4927-2024-ie00002.svg" width="9pt" height="16pt" src="bg-21-4927-2024-ie00002.png"/></svg:svg>) and iodide (I−), is sensitive to the prevalence of oxic vs. anoxic conditions. However, although I /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="57ee8123d9c9aefcf23d9c7f6463c158"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-4927-2024-ie00003.svg" width="8pt" height="14pt" src="bg-21-4927-2024-ie00003.png"/></svg:svg> Ca ratios are increasingly commonly being measured in ancient carbonate samples, a fully quantitative interpretation of this proxy requires the availability of a mechanistic interpretative framework for the marine iodine cycle that can account for the extent and intensity of ocean deoxygenation in the past. Here we present and evaluate a representation of marine iodine cycling embedded in an Earth system model (“cGENIE”) against both modern and paleo-observations. In this framework, we account for IO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="8c72af1edd6d67ed562efcaf5163d22b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-4927-2024-ie00004.svg" width="9pt" height="16pt" src="bg-21-4927-2024-ie00004.png"/></svg:svg> uptake and release of I− through the biological pump, the reduction in ambient IO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="76bbd0535ad9c3e987722e2e722d5d00"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-4927-2024-ie00005.svg" width="9pt" height="16pt" src="bg-21-4927-2024-ie00005.png"/></svg:svg> to I− in the water column, and the re-oxidation of I− to IO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="78ed0f7e81615226176402cdd6a1afd5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-4927-2024-ie00006.svg" width="9pt" height="16pt" src="bg-21-4927-2024-ie00006.png"/></svg:svg>. We develop and test a variety of different plausible mechanisms for iodine reduction and oxidation transformation and contrast model projections against an updated compilation of observed dissolved IO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="fa1148a5a7ab62133104fb46bf612014"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-4927-2024-ie00007.svg" width="9pt" height="16pt" src="bg-21-4927-2024-ie00007.png"/></svg:svg> and I− concentrations in the present-day ocean.